PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN KERAMIK PORSELIN DAN KACA LISTING DI BURSA EFEK INDONESIA PERIODE 2009-2014 - Monika, Gina; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of working capital management on profitability on ceramic porcelain and glass companies listing on the Indonesia Stock Exchange period 2009-2014. Working capital used as an independent variable (X) is with indicators of cash turnover, inventory turnover, and receivable turnover. While used as the dependent variable (Y) is profitability (return on investment).This study uses secondary data that is the annual financial report of porcelain and glass ceramics companies listed in Indonesia Stock Exchange period 2009-2014. Sampling was done by purposive sampling sampling which used 5 porcelain and glass ceramics company. The analysis technique used is simple linear regression, multiple linear regression, coefficient of determination test, t test, and f test. Data analysis using linear regression analysis with SPSS 21 software.From result of research indicate that working capital variable consist of cash turnover, inventory turnover and partial receivable turnover (t test) and simultaneously (F test) there is no influence to profitability (ROI).Keywords: Working Capital, ROI